2017
DOI: 10.1007/s00401-017-1702-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of T cell target antigens in glioblastoma stem-like cells using an integrated proteomics-based approach in patient specimens

Abstract: Glioblastoma (GBM) is a highly aggressive brain tumor and still remains incurable. Among others, an immature subpopulation of self-renewing and therapy-resistant tumor cells-often referred to as glioblastoma stem-like cells (GSCs)-has been shown to contribute to disease recurrence. To target these cells personalized immunotherapy has gained a lot of interest, e.g. by reactivating pre-existing anti-tumor immune responses against GSC antigens. To identify T cell targets commonly presented by GSCs and their diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 89 publications
2
19
0
Order By: Relevance
“…We applied mRNAsi-based WGCNA and identified the module that was associated with BCSC characteristics. [21]. It has also been demonstrated that significant anti-CSC immunity was induced by dendritic cell vaccine basing on CSC both in vitro and in immune-competent hosts [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…We applied mRNAsi-based WGCNA and identified the module that was associated with BCSC characteristics. [21]. It has also been demonstrated that significant anti-CSC immunity was induced by dendritic cell vaccine basing on CSC both in vitro and in immune-competent hosts [8,22].…”
Section: Discussionmentioning
confidence: 99%
“…DEPArray™ is an advanced and highly automated instrument, which complements the capabilities of blood enrichment technologies to deliver pure individual cells suitable for an accurate molecular characterization. The versatility of DEPArray™ has been largely demonstrated by different research groups .…”
Section: Discussionmentioning
confidence: 99%
“…To identify T-cell target antigens, we conducted a two-dimensional tumor proteome fractionation by injecting 2.5 mg of tumor lysates into the ProteomeLab Two-dimensional Protein Fractionation System (PF2D; Beckman Coulter) as described previously (ref. 19; Fig. 1A).…”
Section: Pf2d Liquid Chromatographymentioning
confidence: 93%
“…1D protein fractions were further separated in the second dimension (2D) by reversed phase high-pressure liquid chromatography. Selected fractions were loaded on dendritic cells (DC) generated from blood-derived monocytes of corresponding patients as described (19) and used for immunological testings (IFNg ELISpot) with purified T cells from the same patients ( Fig. 1B and C).…”
Section: Pf2d Liquid Chromatographymentioning
confidence: 99%